The Effect of Study Group by Using Simulation Games to Increase Student's Speaking Ability in SMPN 2 Dewantara - Affini Yusza (Aksaqila International Humanities and Social Sciences [AIHSS] Journal, 2022)
The objective of this research was to increase students’ speaking ability in SMPN 2 Dewantara. This research classified as an action research. The subject of this research were 75 students of class VIII of SMPN 2 Dewantara. It was conducted in two classes in experiment. The data were experiment and control group. The data were obtained through observations and playing simulation games. The research applies pre-test and post-test design. The pre-test is given before the students received the treatment. The form of pre-test and post-test for experimental and control class is the same. It is intended to get the effective method in students’ achievement. The actions implemented in this research were simulation games in the teaching and learning process of speaking, implementing simulation games based activities, giving feedbacks to students’ performances, accustoming students to opening dictionaries, giving handouts as daily materials, and giving rewards the active students. The results of the research showed that the simulation games in the teaching and learning process of speaking was believed to be effective to increase the students speaking ability. The students’ motivation increased. They were more enthusiastic in learning speaking. Moreover, the students were interested in various materials presented by the teacher. They could get involved actively in the speaking learning process. Furthermore, the result of the research also showed that the improvement on the teaching and learning process affected the improvement on the students’ speaking ability.